The Role of Sound Pressure Level and Sound Types in achieving Comfortable acoustic environment for city centers (Al-Karrada as selective district in Baghdad city) - Hasan, Susan Abed (Nahrain University College of Engineering Journal, 2015)
The Acoustic environment represents all the sound that surrounds mankind and that it can interact with the daily life and communicate with members of the community. The importance of acoustic environment in urban centers cause of the diversity and plurality of the sounds resulting from human activities of daily life. This requires designers and urban planners give the required importance in the design of the acoustic environment of cities and in accordance with the requirements and objectives of the present era. This research submits a hypotheses question about the role of sound pressure levels and types in human evaluate the comfortable in acoustical environment for city centers, the research hypotheses is that sound pressure levels and types are important in achieving the comfortable acoustic environment for city centers and for city of Baghdad specifically. This research based on analytical methods and study fielded measurements for sound levels pressure as a first stage, an intensive questionnaire survey was carried out for the recipient in the sound environment as a second stage to submit their of sound environment and the acceptance for it. Al- Karrada district in Baghdad city was choice as an example of the pattern of the acoustic environment in the center of Baghdad, which uses varied between residential, commercial and administrative. Search results showed the presence of high proportions of sound levels generated by the voices of motor vehicles and construction works affecting negatively in the acoustic environment comfort according to the standards measurement accepted levels of the noise, and then its impact on the social aspects of the environment and economic development. Then search made a number of conclusions and recommendations for planners and urban designers to provide a comfortable acoustic environment in urban centers in general and the city of Baghdad specifically.